2008
DOI: 10.1111/j.1742-4658.2008.06668.x
|View full text |Cite
|
Sign up to set email alerts
|

Influential factor contributing to the isoform‐specific inhibition by ATP of human mitochondrial NAD(P)+‐dependent malic enzyme

Abstract: Malic enzymes are a family of oxidative decarboxylases that catalyze the oxidation of L-malate to pyruvate with accompanying reduction of NAD(P) + to NAD(P)H and release of CO 2 [1][2][3][4][5][6][7]. The enzyme requires a divalent metal ion (Mn 2+ or Mg 2+ ) for enzyme catalysis [8,9]. In addition, the metal ion is Human mitochondrial NAD(P) + -dependent malic enzyme (m-NAD-ME) is a malic enzyme isoform with dual cofactor specificity, ATP inhibition and substrate cooperativity. The determinant of ATP inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 46 publications
(73 reference statements)
1
13
0
Order By: Relevance
“…However, the double mutant K346S/Q362K shows slight improvement in decreasing K m,NADP and increasing k cat,NADP , suggesting that Ser-346 plays a supplementary role in cofactor preference of the human m-NAD(P)-ME isoform. We have also suggested that the role of Lys-346 in human NAD(P)-ME is associated with the isoform-specific ATP inhibition (35). In this paper, we further demonstrate that human enzyme with the K346S mutation (K346S, K346S/Y347K, K346S/Q362K, and K346S/Y347K/Q362K) is much less inhibited by ATP and has a larger K i,ATP value than those enzymes without K346S (Fig.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…However, the double mutant K346S/Q362K shows slight improvement in decreasing K m,NADP and increasing k cat,NADP , suggesting that Ser-346 plays a supplementary role in cofactor preference of the human m-NAD(P)-ME isoform. We have also suggested that the role of Lys-346 in human NAD(P)-ME is associated with the isoform-specific ATP inhibition (35). In this paper, we further demonstrate that human enzyme with the K346S mutation (K346S, K346S/Y347K, K346S/Q362K, and K346S/Y347K/Q362K) is much less inhibited by ATP and has a larger K i,ATP value than those enzymes without K346S (Fig.…”
Section: Discussionsupporting
confidence: 51%
“…Recent works on the Ascaris enzyme indicate that changing this and other residues in the cofactor-binding site have only detrimental effects on cofactor binding (33,34). Lys-346 in human m-NAD(P)-ME has minor effects on determining the cofactor preference, but the positive charge of this residue has been identified as having a significant impact on the isoform-specific ATP inhibition (35). Residue 347 also displays an isoform-specific distribution as a Lys in c-NADP-ME but as Tyr or Phe in m-NAD(P)-ME (Fig.…”
Section: Malic Enzyme (Me)mentioning
confidence: 99%
See 1 more Smart Citation
“…Dissimilar to the other two isoforms, m-NAD(P)-ME binds malate cooperatively, and it can be allosterically activated by fumarate; the sigmoidal kinetics observed with cooperativity is abolished by fumarate (9 -12). Mutagenesis and kinetic studies demonstrated that ATP is an active-site inhibitor, although it also binds to the exo sites in the tetramer interface (13)(14)(15). Structural studies also revealed an allosteric binding site for fumarate residing at the dimer interface.…”
mentioning
confidence: 99%
“…1A). In the ME family, Ascaris suum and human m-NAD(P)-ME were found to be activated by fumarate (11,(15)(16)(17)31). However, the relationship between enzyme regulation and subunit-subunit interaction is still unclear.…”
mentioning
confidence: 99%